Subjective Norms as Determinants of University Students ' Response to Covid-19 Vaccination Call During the Pandemic Era: Results from a Qualitative Inquiry - Seguya, Swaib; Kafanabo, Eugenia J.; Mauki, Chris M. (Papers in Education and Development, 2024)
Students ' health-seeking behaviour cannot be fully detached from the influence of subjective social norms since they prescribe behaviours approved by their social affiliations. This study aimed to explore the influence of parents ' and peers ' subjective norms on students ' responses to COVID-19 vaccination in Tanzania. The findings from thirty-three interviewees who were reached by means of purposive and convenience sampling techniques revealed that parents ' actual subjective norms and peers ' injunctive norms influenced the students ' response to vaccination. The evidence suggests a strong influence of norms on students ' health-seeking behaviour, mainly when injunctive norms are reflected in the descriptive norms. Health promotion interventions should not underestimate the power of norms. Keywords: peer influence, parents ' norms, Covid-19 vaccination, university students